2015
DOI: 10.1016/s1474-4422(14)70251-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for neuropathic pain in adults: a systematic review and meta-analysis

Abstract: Summary Background Neuropathic pain is difficult to treat. New treatments, clinical trials and standards of quality for assessing evidence justify an update of evidence-based recommendations for its pharmacological treatment. Methods The Neuropathic Pain Special Interest Group (NeuPSIG) of the International Association for the Study of Pain conducted a systematic review of randomised double-blind studies of oral and topical pharmacotherapy for neuropathic pain, including unpublished trials (retrieved from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
2,119
5
90

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 3,086 publications
(2,398 citation statements)
references
References 67 publications
35
2,119
5
90
Order By: Relevance
“…Thirteen from 15 (87%) patients in the amitriptyline group had ≥50% cough improvement compared to one from 13 (8%) patients in the codeine/guaifenesin group [meta-analysis, Figure 4], number needed to treat (NNT) = 1.3. Combined NNT for 15 studies assessing amitriptyline (25–150 mg/day) for neuropathic pain is 3.6 (95% CI 3.0–4.4) [52]. There were no adverse effects of amitriptyline reported for this study (Table 4) but there was high risk of bias (Figure 2).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Thirteen from 15 (87%) patients in the amitriptyline group had ≥50% cough improvement compared to one from 13 (8%) patients in the codeine/guaifenesin group [meta-analysis, Figure 4], number needed to treat (NNT) = 1.3. Combined NNT for 15 studies assessing amitriptyline (25–150 mg/day) for neuropathic pain is 3.6 (95% CI 3.0–4.4) [52]. There were no adverse effects of amitriptyline reported for this study (Table 4) but there was high risk of bias (Figure 2).…”
Section: Resultsmentioning
confidence: 90%
“…This corresponds to a NNT of 3.6. The combined NNT for 14 RCTs of gabapentin (900–3600 mg/day) for neuropathic pain is 6.3 (95% CI 5.0–8.3) [52]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled studies have demonstrated efficacy and safety of the capsaicin patch in the treatment of PNP (Backonja et al., 2008; Simpson et al., 2008; Irving et al., 2011; Mou et al., 2013), and it is recommended as a second‐line treatment option for the condition, (Finnerup, Attal et al., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Managing patients with PNP is challenging (Dworkin et al., 2007, 2010; Finnerup et al., 2010; Finnerup, Attal et al ., 2015); it often becomes chronic, with marked long‐term reductions in health‐related quality of life (HRQOL) (O'Connor, 2009), decreased individual productivity and increased patient and healthcare expenditure (Rodríguez et al., 2007; Navarro et al., 2011). Aetiologies range from mechanical and inflammatory diseases to injury and nerve compression (Hall et al., 2006).…”
Section: Introductionmentioning
confidence: 99%